Mengintegrasikan Konsep Vygotsky dalam Pendidikan Islam: Upaya Orang Tua dalam Memaksimalkan Potensi Anak - Tamrin Fathoni (https://ejournal.insuriponorogo.ac.id/, 2023)
In this work, the purpose of writing is to analyze Vygotsky's concept in Islamic education and parents' efforts to maximize children's potential. This study uses the literature review method to analyze literature and related research on the integration of Vygotsky's concepts in Islamic education and the role of parents in maximizing children's potential. The approach used is a qualitative approach, with data collected from literature, scientific journals, books, theses, and other relevant sources. Data will be analyzed through literature study techniques and content analysis to identify findings that are relevant to the research theme. The results of this work are Vygotsky's approach to Islamic education emphasizing social interaction and environmental influences in child development. Parents use semiotic variations and interactions with knowledgeable peers for religious learning. Collaboration between parents and schools in creating an educational environment that supports social interaction and the use of semiotic variations will be effective in developing individuals who have good morals and are able to apply religious teachings in everyday life.